Knowledge and practice regarding prevention of surgical site infection among nursing students at School of Health Sciences, Universiti Sains Malaysia (USM) - Aziz, Noor 'Ain Che (Universiti Sains Malaysia, 2013)
Surgical site infection (SSI) is a significant clinical problem leading to morbidity and mortality for hospitalized surgical patients. The goal of this descriptive crosssectional study was to determine the level of knowledge and practice, examined the difference between knowledge and practice and also their relationship regarding prevention of SSI among final year Diploma nursing and Bachelor degree nursing at School of Health Sciences, Universiti Sains Malaysia (USM). Seventy two final year nursing students were recruited in this study using systematic randomized sampling. Data were collected from February to March 2013 using self-report questionnaires and analyzed using SPSS version 20. Ethical approval was obtained from Research Ethics Committee (Human), USM. The results revealed overall level of knowledge regarding prevention of SSI were at low level for Diploma nursing (M=63.00, SD=9.81) and Bachelor degree nursing (M= 65.22, SD= 12.67). Meanwhile, overall level of practices were at high level for Diploma nursing (M= 86.51, SD= 7.78) and also Bachelor degree nursing (M= 81.77, SD= 11.48). There were no significant difference of knowledge regarding prevention of SSI (p = 0.408) but significant difference of practice regarding prevention of SSI between final year Diploma and Bachelor degree nursing students (p = 0.045). The study also found there was a weak relationship between knowledge and practice regarding prevention of SSI for Diploma nursing (r = -0.050, p - 0.773) and Bachelor degree nursing (r = 0.088, p = 0.612). Based on findings, it was recommended that the syllabus in Nursing Curriculum should be reviewed and added comprehensive program regarding prevention of SSI. Extensive clinical posting should be considered for nursing students to improve their specific skills on prevention of SSL